The Competence, Motivation, Human Resources Management And Leadership Style Effect On Employee Performance At The Education Office Of Tangerang District - Warso, Eko; Wahab, A. Azis; Mudrikah, Achmad; Gaffar, M. Andriana (CV. Inara, 2022)
The purpose of this study was to examine the effect of competence, motivation, human resource management and leadership style on employee performance (a case study on employees of the Tangerang Regency Education Office. The analytical method used is descriptive quantitative method with multiple correlation and multiple regression approaches and uses the program SPSS version 25.0 Based on the results of the data analysis equation, the regression obtained is as follows:Y = 15,414 + 0.486X1 + 0.261X2 - 0.221X3 + 0.346 X4.Based on hypothesis testing using the T test that leadership style and motivation have a positive and significant effect on employee performance. The results of the study simultaneously using the F test, showed that all independent variables had a significant effect on employee performance. The correlation coefficient value is 0.613. With these results, it is found that there is a strong correlation for the influence of competence, motivation, human resource management and leadership style on the performance of Tangerang Regency Education Office employees, because the coefficient value is between 0.50 to 0.75. While the value of the coefficient of determination of the performance of the Tangerang Regency Education Office employees is shown by the Adjusted R Square value of 0.327, this means that the contribution of the influence of competence, motivation, human resource management and leadership style on the performance of Tangerang Regency Education Office employees is 32.7% while the remaining 67.3% is influenced by other variables. Outside the variables studied.